Surface modification of He pre-exposed tungsten samples by He plasma impact in the divertor manipulator of ASDEX Upgrade. (August 2017) - Brezinsek, S.; Hakola, A.; Greuner, H.; Balden, M.; Kallenbach, A.; Oberkofler, M.; De Temmerman, G.; Douai, D.; Lahtinen, A.; Böswirth, B.; Brida, D.; Caniello, R.; et al.
Abstract: Tungsten (W) will be used as material for plasma-facing components (PFCs) in the divertor of ITER and interact with Helium (He) ions either from initial He plasma operation or from Deuterium-Tritium (DT) fusion reactions in the active operation phase. Laboratory experiments reported that in a specific operational window of impact energy, ion fluence, and surface temperature ( Ein ≥ 20 eV, ϕ ≥ 1 × 10 24  He + m B t = 2.5 T, I p = 0.8 M A, P a u x ≃ 8.0 M W Tsurf ≥ 1000 K) a modification of W surfaces occurs resulting in the formation of He-induced W nanostructures. Experiments in ASDEX Upgrade H-mode plasmas ( E i n = 37 k e V  T, ϕ ≃ 0.75 × 10 24 H e 0 m − 2  MA, Paux ≃ 8.0 MW) in He have been carried out to investigate in detail (a) the potential growth of W nanostructures on pre-damaged W samples incorporating He nanobubbles, and (b) the potential ELM-induced erosion of W nanostructure. Both W surface modifications were generated artificially in the GLADIS facility by He bombardment of W samples at ϕ ≃ 1 × 10 24 H e 0 m − 2  keV (a) to ϕ ≃ 0.75 × 10 24  He 0 m ϕ ≃ 1.6 × 10 24 H e + m − 2 at Tsurf ≃ 1800 K and (b) ϕ ≃ 1 × 10 24  He 0 m − 2 at Tsurf ≃ 2300 K prior to exposure in the divertor manipulator of ASDEX Upgrade. Though in part (a) conditions of W nanostructure growth with a total He ion fluence of ϕ ≃ 1.6 × 10 24  He + m − 2 and peak He ion impact energies above 150 eV were met, no growth could be detected. In part (b) lower density plasmas with more pronounced type I ELMs, carrying energetic He ions in the keV range, were executed with the strike-line positioned on 2 µm thick W nanostructure accumulating a fluence of ϕ ≃ 0.8 × 10 24  He + m − 2 . Post-mortem analysis revealed that co-deposition by predominantly W, and Boron (B), eroded at the main chamber wall and transported into the divertor, took place on all W samples. Erosion of W nanostructure or its formation was hindered by the fact that the outer divertor at the location of the samples was turned under these He plasma conditions into a net deposition zone by W, B and Carbon (C) ions. The surface morphology with large roughness and effective surface area act as a catcher for the impinging impurities. Thus, apart from operation in the existence diagram of W nanostructure with respect to Tsurf, ϕ, and Ein, also the impinging impurity flux contribution needs to be considered in predictions concerning the formation of W nanostructures.